Chemical Characteristics and Antioxidant Activity of Instant Drink Lemon Kalamansi (Citrus microcarpa) with Addition of Clove Leaf (Eugenia carryophyllus) and Nutmeg Meat (Myristica fragrans) Extracts - Edam, Mariati; Suryanto, Edi; Djarkasi, Gregoria S. S. (Pascasarjana Unsrat, 2016)
Lemon kalamansi, clove leaf and meat nutmeg have bioactive compounds that have potential as antioxidants so it can serve as raw material for made of instant drink. This study aims to analyze the chemical characteristics and antioxidant activity of instant drink lemon kalamansi with the addition of clove leaf and meat nutmeg extract. The research method is experimental research with a completely randomized design as many as three levels of treatment with three replications arranged in the form of formulations. The results showed that the instant drink lemon kalamansi characteristics containing antioxidant such as phenolic compounds which range from 24,50-130,51 Âµg/mL (highest in formulation B is the addition of clove leaf extract 20%), vitamin C ranged 278,70-390,55 mg/100 g bahanÂ (highest in formulation B is 390,55 mg/100 g bahan), as well as the activity of antioxidant free-radical scavengers ranged 18,11-46,73% (formulation B, namely the addition 20% of clove leaf extract showed the highest activity in counteract free radicals). Based on the results of this study it can be concluded that the instant drink lemon kalamansi with the addition of meat nutmeg and clove leaf extract contains antioxidant compounds that have potential as functional drinks. Keywords: antioxidant, clove leaf, instant drink, kalamansi, nutmeg meat